Saʿādat Ḥasan Manṭo, apnī taẖlīqāt kī raušanī meṉ - Mahsher Abidi, Syed Mohammad Mohsin (Dārulišāʿat Taraqqī, 1982)
Study and psychological analysis of the works of Saʿādat Ḥasan Manṭo, 1912-1955, Urdu short story writer; includes biographical information
Includes bibliographical references (pages 124-128)
Keywords: Manṭo; Saʿādat Ḥasan; Criticism; interpretation; etc